Study on the influence of foreign direct investment on innovations in enterprises in Poland using the ECM model - Salamaga, Marcin (Publishing House of Wroclaw University of Economics and Business, 2023)
In many theories of economics and empirical research, foreign direct investment (FDI) is perceived as a potential technology transfer channel bringing tangible benefits to FDI exporting countries and host countries. In light of some theories, such as Vernon’s product life cycle theory or Dunning’s pull factor theory, and the results of empirical research, the impact of inward FDI flows inhibits the development of innovation or has a neutral effect on innovation in the host country. In the era of the growing internationalisation of enterprises, and the search for opportunities for enterprises to compete on the domestic and foreign markets, innovation is becoming one of the most important elements of building a competitive advantage. Innovation and new technologies are also of fundamental importance for Polish enterprises that want to compete effectively. The question is, to what extent FDI in Poland favours this process, and to what extent limits it? In the empirical studies conducted so far for the Polish economy in the field of the relationship between the inflow of FDI and innovation, there are not many models that would allow to describe the cause-effect relationship between the discussed categories. The authors of this article attempt to fill this research gap. The main goal was to examine the directions and intensity of the impact of foreign direct investment on the level of innovation of enterprises in the main sectors of the economy in Poland. The study used, among others, panel data models with error correction mechanism (ECM) and the Granger causality test. The results confirmed the positive impact of foreign direct investment on the innovativeness of enterprises both in the industrial sector and in the service sector. Moreover, the impact of FDI on the innovativeness of enterprises in the industrial sector turned out to be stronger than the impact on the innovativeness of companies from the service sector.
Argumenta Oeconomica, 2023, Nr 1 (50), s. 119-136
Keywords: innovation; foreign direct investment; ECM; granger causality